ChemInform Abstract: Hexafluoridotechnetate(IV) Revisited. Issue 34 (1st August 2013) - Balasekaran, Samundeeswari Mariappan; Molski, Matthias; Spandl, Johann; Hagenbach, Adelheid; Alberto, Roger; Abram, Ulrich
Abstract New and improved syntheses for [TcF6]2‐ salts and single crystal structures for (VI) and (VIII) are reported.